Thermochemical pretreatments for agricultural residue ash production for concrete - Ataie, Feraidon F.; Riding, Kyle A. (My University, 2013)
Agricultural residue ash is known to be a very reactive source of supplementary cementitious material (SCM) for use in concrete. The influence of thermochemical pretreatments on the reactivity of agricultural residue ash (ARA) for use as an SCM was studied. It was shown that pretreatments are effective in partial removal of alkali metals and other impurities out of both wheat straw and rice straw leading to ARA with lower loss on ignition (LOI), higher internal surface area, and higher amorphous silica content than that of unpretreated ARA. It was shown that the ash alkali content correlated with the ash LOI and amorphous silica content. When used at a cement replacement rate of 20% by mass, pretreated ARA accelerated the hydration of cement paste samples while unpretreated ARA retarded the cement hydration. Pretreatments were found to increase ARA reactivity as measured by calcium hydroxide content reduction with time. ARA increased compressive strength of mortar samples by 25% when used as 20% replacement of cement in the samples. It was found that the calcium hydroxide content of paste samples and mortar compressive strength were correlated to the amorphous silica content of the ash.
Keywords: Thermochemical pretreatments; Ashes; Concrete; Agricultural wastes; Recycling; Pozzolanic reactivity